WED 190 Teriflunomide pregnancy registry: design and enrolment. Issue 10 (13th September 2018) - David, Rog; Christine, Lebrun-Frenay; Nicola, Seferta; Myriam, Benamor; Susan, Colilla; Philippe, Truffinet; Angelo, Ghezzi
Abstract : Introduction: Teriflunomide is contraindicated in pregnancy, based on developmental toxicity in rats and rabbits. During clinical development, despite requirements for contraceptive use, some pregnancies occurred. There were no signs of structural or functional deficits in newborns. Methods: The multinational, prospective, observational International Teriflunomide Pregnancy Exposure Registry is enrolling teriflunomide-exposed pregnant women with MS. Signed informed consent is obtained prior to enrolment. In the UK, healthcare professionals submit information to the National Coordinating Centre (Manchester, UK). Infants are followed until 1 year old. Pregnancy outcomes, including birth defects and infant characteristics, are collected. Target recruitment: 196 women to achieve 104 live births, providing 80% power to detect 3.95-fold increase in risk of birth defects associated with teriflunomide exposure vs the European Surveillance of Congenital Anomalies (EUROCAT) network. Results: As of 26/04/2017, 14 patients have been recruited from 7 European countries (none in the UK). Six healthy babies have been born to date. One patient had an elective termination not motivated by abnormal prenatal test results or concerns regarding potential birth defects. Conclusion: This registry aims to provide data on pregnancy outcomes and infant development from teriflunomide-exposed women, which may help physicians provide better patient advice. Study supported by Sanofi.